Kelayakan Finansial Usaha Perkebunan Jeruk Siam di Desa Sekaan Kecamatan Kintamani Selatan Kabupaten Bangli - CITA, I DEWA PUTU GEDE ANOM MAHA ADHI; SARJANA, I DEWA GEDE RAKA; RANTAU, I KETUT (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.5, No.4, Oktober 2016, 2016)
Business Feasibility of Tangerine Plantationin the Village of Sekaan, Sub-District of Southern Kintamani , the Regency of Bangli The roles of agriculture in the national economic development are asthe driving force of economic growth through the agro-industry, as a provider and developer of the market for the products and services of non-agricultural sectors, as capital accumulation and qualified workforce and as the conservation of natural resources for sustainable development. One of the agricultural commodities that has important and strategic positions are citrus fruits. Data from the Department of P3 (agriculture, horticulture, and forestry) of Bangli Regency in 2014 showed that the total population of citrus crop in Bangli Regency amounted to 4,084,168 trees, within a period of five years from 2009 until 2013, citrus production has fluctuated.One of the tangerine farms in the Province of Bali is located in the village of Sekaan, Sub-District of Southern Kintamani, Bangli Regency. Therefore, the study was conductedto analyze the financial feasibility, and obstacles faced in running the tangerine plantation business for 10 years. In the financial feasibility, the aspects discussed include: net present value, net benefit / cost ratio, internal rate of return, payback period and sensitivity analysis that were discussed descriptively and quantitatively. Theresults showed that the tangerine farming business in the village of Sekaan, Sub-District of Southern Kintamani, Bangli Regency is feasible to be continued.
Keywords: tangerine plantation business, financial feasibility, obstacle